Fate of Barium Sulfate Nanoparticles Deposited in the Lungs of Rats - Molina, Ramon M. (Sci Rep, 2019)
We have shown that barium [from BaSO(4) nanoparticles (NPs)] was cleared from the lungs faster than other poorly soluble NPs and translocated mostly to bone. We now studied barium biokinetics in rats during Study 1: two-year inhalation exposure to 50 mg/m(3) BaSO(4) NP aerosols, and Study 2: single intratracheal (IT) instillation of increasing doses of BaSO(4) NPs or BaCl(2). Study 1 showed that lung barium content measured by inductively coupled plasma mass spectrometry increased during 360 days of BaSO(4) NP aerosol exposures. An equilibrium was established from that time until 2 years. Barium concentrations in BaSO(4)-exposed animals were in the order (lungs > lymph nodes > hard bone > bone marrow > liver). In Study 2, there was an increase in lung barium post-IT instillation of BaSO(4) NPs while barium from BaCl(2) was mostly cleared by day 28. Transmission electron microscopy showed intact BaSO(4) NPs in alveolar macrophages and type II epithelial cells, and in tracheobronchial lymph nodes. Using stimulated Raman scattering microscopy, specific BaSO(4) Raman spectra were detected in BaSO(4) NP-instilled lungs and not in other organs. Thus, we posit that barium from BaSO(4) NPs translocates from the lungs mainly after dissolution. Barium ions are then incorporated mostly into the bone and other organs.